Improvement Standard Operating Procedures Banana Chips Production In CV. Zanana Indonesia - Diandra Puteri Salsabilla; Totok Pujianto; Selly Harnesa Putri (JASc (Journal of Agribusiness Sciences), 2022)
In order to improve national standards, Micro Small and Medium Enterprises (MSME) empowerment is considered to be one of the right solutions. Currently, many MSME already have standards but are still considered incomplete in the implementation of the production process. This research takes a case study in CV. Zanana Indonesia is an MSME engaged in the food sector and producing banana chips. Currently, the business already has Standard Operating Procedures but does not have work instructions and production activity forms. This study aims to improve the SOP and design work instructions and forms of production process activities. The primary data used is interviews with employees about the production of banana chips meanwhile secondary data used is about business management, business model and production process. Interview by production employees using the interview guide, observations are made directly in production and study literature using existing business data and related journals. The results of the design are in the form of 11 SOP for the production, 8 work instructions, and 4 forms for the production. The level of importance of the SOP design classified as important (76,26%), the level of implementation has 75,96% and improvement of the SOP design has 74,05%.